2001
DOI: 10.1046/j.1439-0418.2001.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural enemy complex of the gypsy moth, Lymantria dispar (Lep., Lymantriidae) in different phases of its population dynamics in eastern Austria and Slovakia – a comparative study

Abstract: Parasitism and pathogen mortality of Lymantria dispar were compared between host populations of different densities in Slovakia and Austria. Over a period of 4 years, L. dispar eggs, larvae, and pupae were collected in a stage‐specific manner at three mixed oak stands in each country and reared in the laboratory to assess parasitoid and pathogen mortality. At sites with low host densities, L. dispar abundance was artificially augmented by exposing egg masses and young larvae. We ascertained marked differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 15 publications
(27 reference statements)
2
60
1
Order By: Relevance
“…Though spatially and temporally restricted, they parasitized a high proportion of 221 above-ground cocoons in summer, indicating that Monodontomerus may be able to limit the population growth of sawflies that results from a bivoltine development. Hoch et al (2001) observed a rapid reaction of the parasitoid Glyptapanteles liparidis to artificially increased populations of Lymantria dispar. Such spatial and/or temporal density-dependent responses of natural enemies may prevent the development of outbreaks from "hot spots" of increased herbivore density.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Though spatially and temporally restricted, they parasitized a high proportion of 221 above-ground cocoons in summer, indicating that Monodontomerus may be able to limit the population growth of sawflies that results from a bivoltine development. Hoch et al (2001) observed a rapid reaction of the parasitoid Glyptapanteles liparidis to artificially increased populations of Lymantria dispar. Such spatial and/or temporal density-dependent responses of natural enemies may prevent the development of outbreaks from "hot spots" of increased herbivore density.…”
Section: Discussionmentioning
confidence: 97%
“…Parasitoids are generally considered to be key natural enemies determining these population dynamics (Kidd & Jervis, 1997). On the other hand, it is suggested that strong fluctuations in host density may also create profound changes in the species composition of a parasitoid community due to the occurrence of high vs. low density specialists (Pschorn-Walcher, 1977;Mills, 1990;Hoch et al, 2001). Furthermore, varying environmental conditions may increase or restrict the abundance of parasitoid species by determining the presence or absence of other essential resources (Simmons et al, 1975;Roland et al, 1997;Lewis & Whitfield, 1999;Quayle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(as reviewed in McManus and Solter, 2003). More typically, however, microsporidia occur at lower enzootic levels (Novotny, 1989;Hoch et al, 2001;Pilarska et al, 1998) and are detected in most populations in Europe. They must, therefore, have effective paths for disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…It was also often observed in mixed infections together with bacteria or fungi. Mortality by microsporidia was usually low (<5%); however, species of Entomophthorales have never been reported (Fuester, Drea, Gruber, Hoyer, & Mercadier, 1983;Hoch, Zúbrik, Novotný, & Schopf, 2001;Solter et al, 2010;Weiser, 1998). …”
Section: Biocontrol Science and Technology 711mentioning
confidence: 99%